2018
DOI: 10.1007/s10459-018-9839-9
|View full text |Cite
|
Sign up to set email alerts
|

The Jefferson Scale of Empathy: a nationwide study of measurement properties, underlying components, latent variable structure, and national norms in medical students

Abstract: The Jefferson Scale of Empathy (JSE) is a broadly used instrument developed to measure empathy in the context of health professions education and patient care. Evidence in support of psychometrics of the JSE has been reported in health professions students and practitioners with the exception of osteopathic medical students. This study was designed to examine measurement properties, underlying components, and latent variable structure of the JSE in a nationwide sample of first-year matriculants at U.S. college… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

22
174
2
17

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 196 publications
(249 citation statements)
references
References 74 publications
22
174
2
17
Order By: Relevance
“…33,38 Conversely, JSE scores were negatively correlated with personal qualities that are detrimental to relationship building, including aggression-hostility, 26,39 indicators of burnout such as depersonalization and emotional exhaustion, 36,40,41 and neuroticism. 42 In a 2018 study 43 (using POMEE data), we found strong evidence in support of the measurement properties, underlying components, and latent variable structure of the JSE in a nationwide sample of first-year matriculants to osteopathic medical schools.…”
Section: Researchers In the United States And Abroad Havementioning
confidence: 79%
“…33,38 Conversely, JSE scores were negatively correlated with personal qualities that are detrimental to relationship building, including aggression-hostility, 26,39 indicators of burnout such as depersonalization and emotional exhaustion, 36,40,41 and neuroticism. 42 In a 2018 study 43 (using POMEE data), we found strong evidence in support of the measurement properties, underlying components, and latent variable structure of the JSE in a nationwide sample of first-year matriculants to osteopathic medical schools.…”
Section: Researchers In the United States And Abroad Havementioning
confidence: 79%
“…Internal consistency reliability, determined by Cronbach's coefficient alpha, is mostly reported in the 0.70s and 0.80s, 6 and stability of scores over time by test–retest reliability (in the 0.60s) has been reported in physicians, 20 allopathic medical students 13 and osteopathic medical students 10 …”
Section: Methodsmentioning
confidence: 99%
“…Empirical research shows that medical students’ empathy is positively associated with how faculty members rate their clinical competence, 7 and physician's empathy has been found to predict positive clinical outcomes 8,9 . Significant correlations have also been reported between medical student's empathy and personality attributes conducive to relationship building (for a review see Hojat et al 10 and Hojat et al 11 ). Conversely, negative correlations have been found between empathy in medical and other health professions students and personal qualities detrimental to interpersonal relationships .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations